O arco e flecha como construtores do mundo: a prática tradicional do kyudo e do Potiguara na Paraíba - Sá, Sônia Maria Neves Bittencourt de (2018)
This dissertation in the field of technical studies, and performance management through analysis of the processes of construction of the bow and the arrow potiguara and Kyudo, the traditional Japanese arqueria. In this perspective, the present research is structured from a central question: How the bows and arrows Potiguara and kyudo crossed times and continue their practices today? Anthropological consideration underlying the study is the relationship between continuities and changes, ressignification tradition. In this sense, the general objective outlined was to understand how the arches are constructed, and how the interaction between the arches and craftsmen; the arches and the archers; from an ethnographic approach with the two groups: the artisans of the villages of indigenous lands Potiguara and his archers, as well as between the practitioners of Kyudo. The methodology used consisted of a set of procedures, such as: l. bibliographical and historical about the samurai and Japanese Immigration to the North East of Brazil and of the potiguara warriors; craftsmen and archers involved with the practice of bow and arrows; 2. Mapping bibliographical study on the State of the art in the field of technical studies, and performance management; 3. ethnographic field research between 2016 and 2017 involving several observations, descriptions and dialogue collected among the artisans and practitioners who made dialogue between theorists in the field of technical, management and performance as the reflection axis. The work was divided into three topics: the first for a general approach on the issue of the bow and arrows; the second though of knowledge, nature and the poetics of construction of concrete arches; And in the third, and last, examine the relationship between body and bow and arrows based studies produced support in the field of visual anthropology. In this case, analyze the Potiguaras indigenous games and the festivals of Japan, in João Pessoa the year 2016 and 2017, respectively. In addition to this dissertation ethnographic approaches held together both groups increased the production of a video and a photo collection about the form of construction and handling of the arches. The study signaled the ressignification of the contemporary bow and arrow as a sportif process. Before being a conclusive work, the study of the bow and arrows between these two groups, sought to be more reflective and, above all, provocative and open new paths to be set for a greater understanding of the technical connection, handling and performance.